A BIM-enabled framework for evaluating mega construction projects through sustainable development goal indicators - Hasan, Sada; Isik, Zeynep; Demirdogen, Gokhan (ELSEVIER, 2026)
There is a growing need to align construction sector practices with the UN Sustainable Development Goals (SDGs). However, mechanisms for integrating these goals into project-level decision-making processes remain unsystematic and limited, particularly in the early stages. This research aims to develop a viable and validated assessment framework that links Building Information Modeling (BIM) functions to SDG indicators during the planning and design phases of large-scale projects. The multi-stage methodology included a comprehensive literature review on the relationship between BIM functions and the SDGs, followed by a two-round Delphi evaluation to validate the significance of these correlations. A model for evaluating the stages was then developed based on Business Process Modeling Notation (BPMN) and tested on a case study. The literature review identified 276 potential correlations, which were narrowed down to 113 highly significant correlations after statistical validation (Cronbach's alpha = 0.981 and 0.992). Applying the framework to a mega-project case study revealed significant phase variations in the level of alignment with SDG indicators. Alignment reached 64% in the early planning phase, with high performance in energy efficiency (SDG 7.1.2), water use efficiency (SDG 6.4.1), sustainable transport access (SDG 11.2.1), and inclusive urban planning (SDG 11.3.1). During the design phase, the alignment rate dropped to 38%, reflecting relative shortcomings in the integration of renewable energy functionality, governance frameworks, and socioeconomic indicators. Furthermore, integrating BIM applications in the early stages of the case study enhances alignment with SDGs by up to 26% compared to later stages. Therefore, the proposed framework provides a replicable methodological tool to support sustainabilitydriven decision-making and the integration of performance indicators into the digital workflows of large-scale construction projects.
Keywords: Sustainable Development Goals (SDGs); Mega Construction Projects; Assessment Framework; Business Process Modeling Notation (BPMN); INFORMATION MODELING BIM; QUANTITY TAKE-OFF; ENVIRONMENTAL ASSESSMENT; ENERGY EFFICIENCY; DELPHI METHOD; GREEN BIM; DESIGN; WASTE; INFRASTRUCTURE; IMPLEMENTATION; Engineering